2017
DOI: 10.1111/jth.13861
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid receptor‐α regulates synthetic events in human platelets

Abstract: Background Translational control mechanisms in platelets are incompletely defined. Here, we determined whether the nuclear transcription factor RARα controls protein translational events in human platelets. Methods Isolated human platelets were treated with the pan-RAR agonist all-trans-retinoic acid (atRA). Global and targeted translational events were examined. Results Stimulation of platelets with atRA significantly increased global protein expression. RARα protein bound to a subset of platelet mRNAs, as me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…We appreciate the comments from de la Salle et al . regarding our recent findings on all‐ trans ‐retinoic acid as a translational control mechanism in human platelets . We agree with the notion that, when platelet molecular biology studies are performed, highly purified platelet preparations are needed.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…We appreciate the comments from de la Salle et al . regarding our recent findings on all‐ trans ‐retinoic acid as a translational control mechanism in human platelets . We agree with the notion that, when platelet molecular biology studies are performed, highly purified platelet preparations are needed.…”
supporting
confidence: 88%
“…We agree with the notion that, when platelet molecular biology studies are performed, highly purified platelet preparations are needed. As described in this report and others , we utilized a rigorous and validated method in the field of purifying platelets from whole blood . In this method, leukocyte‐immunodepleted suspensions are prepared with anti‐CD45 magnetic beads.…”
mentioning
confidence: 99%
“…Rondina et al described that treatment with all‐trans retinoic acid, which is structurally similar to 9cRA, disrupts the RARα‐Arp2/3 interaction and yields an inhibition of both cytoskeletal rearrangements and platelet spreading. Further, Schwertz et al showed that platelets treated with atRA have altered levels of protein synthesis compared to controls indicating effects on protein regulation. Taking this into account, it seems reasonable that molecules acting as RXR agonists may also affect platelet function through other NRs.…”
Section: Discussionmentioning
confidence: 99%
“… 41 Recent developments have reported that RARα is capable of regulating protein synthesis (including microtubule-associated protein-1 light chain 3 beta 2) in human platelets by binding to a subset of mRNAs and blocking translation. Schwertz et al 66 found that platelets treated with RARα ligand atRA for several hours displayed significantly altered levels of protein synthesis compared to controls.…”
Section: Type II Nrsmentioning
confidence: 99%